Studi persepsi potensi taman kota sebagai taman terapeutik di Taman Kota Lumintang, Denpasar Utara, Bali - Devi Wahyuni, Ni Made; Krisnandika, Anak Agung Keswari; Setiawan, I Gede Bagus Dera (Jurnal Arsitektur Lansekap, 2025)
Urbanization in major cities like Denpasar has heightened mental and physical health challenges due to pollution and life pressures. Green spaces like Lumintang City Park hold potential as therapeutic gardens to reduce stress and enhance psychological well-being, aligning with restorative environment theory. This study aims to assess the existing conditions of Lumintang City Park in terms of hardscape, softscape, social, cultural, and economic aspects, and to evaluate visitors’ perceptions of it as a therapeutic garden based on physical, quality, spatial, vegetation, paving, water elements, and psychological parameters. Conducted at Lumintang City Park, Denpasar, Bali (27,220 m²) from July 2024 to August 2025, the research used a quantitative descriptive survey method. Data were gathered through observation, Likert-scale questionnaires, and literature studies, with a sample of 97 visitors aged 15 and older. Results revealed an average perception score of 3.72 ("Agree"), confirming the park’s effectiveness as a therapeutic medium. Despite areas needing improvement, such as the entrance (3.14) and disability facilities (3.31), Lumintang City Park successfully serves as a multifunctional public space supporting mental health, consistent with the Restorative Environment theory.